2001
DOI: 10.1093/rheumatology/40.2.158
|View full text |Cite
|
Sign up to set email alerts
|

Morphological analysis of knee synovial membrane biopsies from a randomized controlled clinical study comparing the effects of sodium hyaluronate (Hyalgan®) and methylprednisolone acetate (Depomedrol®) in osteoarthritis

Abstract: At least in the medium term, both HY and MP modified a number of structural variables of the synovial membrane of the osteoarthritic human knee towards the appearance of that of normal synovium. The effect was more evident in primary OA than in OA secondary to a traumatic event. This is the first evidence that local hyaluronan injections modify the structural organization of the human knee synovium in OA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(39 citation statements)
references
References 30 publications
3
34
0
Order By: Relevance
“…Results from experimental OA and limited arthroscopic observations in humans indicate that hyaluronan possesses mild chondroprotective and anti-inflammatory activities. [37][38][39] Compared with hyaluronan, intra-articularly administered GlcNAc in normal saline has a much shorter half life (minutes for GlcNAc versus hours for hyaluronan (San-Bao Hwang, unpublished data)). However, in experimental OA GlcNAc demonstrated better disease modifying activity than hyaluronan.…”
Section: Discussionmentioning
confidence: 99%
“…Results from experimental OA and limited arthroscopic observations in humans indicate that hyaluronan possesses mild chondroprotective and anti-inflammatory activities. [37][38][39] Compared with hyaluronan, intra-articularly administered GlcNAc in normal saline has a much shorter half life (minutes for GlcNAc versus hours for hyaluronan (San-Bao Hwang, unpublished data)). However, in experimental OA GlcNAc demonstrated better disease modifying activity than hyaluronan.…”
Section: Discussionmentioning
confidence: 99%
“…Hyaluronic acid concentrations are decreased in the joints of patients with osteoarthritis. [17][18][19][20] Hyaluronic acid is responsible for the viscoelastic component of synovial joint fluid; it is also an effective lubricant, shock absorber, and fluid retainer, especially in weightbearing joints. 21 The exact mechanism through which intra-articular hyaluronic acid promotes decreased joint pain is not clearly understood, but there are numerous proposed mechanisms including upregulation of cartilage synthesis as well as the inhibition of inflammatory cytokines and phagocytic cells.…”
Section: Hyaluronic Acidmentioning
confidence: 99%
“…27 It has also been suggested that low-to mid-weight hyaluronic acid concentrations have better penetration into synovial tissue and may contain some disease-modifying activity, though these benefits have not been demonstrated in clinical studies. 19,22 …”
Section: Hyaluronic Acidmentioning
confidence: 99%
“…vide further evidence that HA injections may be an effective low-risk treatment for TMCJ OA unresponsive to standard medical therapy 4,[11][12][13] . This retrospective open label study evaluated the results of i.a.…”
Section: Six-months Pain Relief and Functional Recovery After Intra-amentioning
confidence: 89%